Coprocessed Excipients: Multifunctional Excipients for Solid Oral, Liquid, Semisolid, Parenteral, and Biological Preparations - Telrandhe, Mr. Umesh B. (Asian Journal of Pharmaceutics (AJP), 2023)
In pharmaceutical dosage forms, the excipient represents a unique and significant substance with equal importance to active pharmaceutical ingredients (API) because it offers numerous benefits to the final formulations. Benefits include filling the tablet’s total volume, enhancing API absorption and bioavailability, and increasing organoleptic properties. However, the diverse nature of excipients, API-excipients incompatibility, moisture absorbing ability, surface acidity of the excipients, crystal nature, and generation of inferior toxic excipients, etc., may create a big problem in selecting appropriate excipients. The excipients high toxicity may substantially impact the formulation and API’s pharmacokinetic and pharmacodynamic nature. It may likely be due to using multiple excipients with incompatible performance. Adopting and implementing cGMP in the pharmaceutical industry can solve the issues related to excipients; however, it still affects the excipients manufacturing process in terms of its time-consuming, high cost, and lengthy approval process. With their multifunctional properties, coprocessed excipients can provide special offers to formulation scientists when manufacturing dosage forms. The need for coprocessed excipients, requirements of excipients to be coprocessed, manufacturing technology, risk and assessment studies, application, and regulatory compliance provide an alternate and promising approach for selecting and using an appropriate combination of existing excipients over the native excipients in the formulation of dosage forms